Oral synechiae: A case presentation of airway and surgical management. (March 2016) - Ho, Thuy-Van T.; Weatherly, Robert A.; Kaye, Alison E.
Abstract: Oral synechiae is a rare craniofacial condition only described by case reports in the literature. This case report features a 1-day-old female twin who was transferred to our hospital for airway management in the setting of an unspecified intraoral anomaly. The patient was taken emergently to the operating room where awake nasal intubation was performed. Closer oral inspection revealed an oral synechia that was released superiorly with cautery. This case highlights a unique patient with an oral synechia who required prompt airway and surgical management. No previous articles have addressed definitive airway stabilization in cases of oral synechiae.